A Projection-Type Method for Solving Various Weber Problems (Journal of Computational Mathematics, 2006)
This paper investigates various Weber problems including unconstrained Weber problems and constrained Weber problems under $l_1,l_2$ and $l_∞$-norms. First with a transformation technique various Weber problems are turned into a class of monotone linear variational inequalities. By exploiting the favorable structure of these variational inequalities, we present a new projection-type method for them. Compared with some other projection-type methods which can solve monotone linear variational inequality, this new projection-type method is simple in numerical implementations and more efficient for solving this class of problems; Compared with some popular methods for solving unconstrained Weber problem and constrained Weber problem, a singularity would not happen in this new method and it is more reliable by using this new method to solve various Weber problems.